Compact asymmetric-slotted-slit patch based circularly-polarized antenna with reactive impedance surface substrate - Agarwal, Kush (2013)
A compact, asymmetric-slotted-slit-microstrip patch, based antenna on a reactive impedance surface (RIS) is proposed and studied for the circularly polarized (CP) radiation.The antenna consists of a slotted-slit-microstrip patch on a RIS substrate. The CP radiation with compact size is achieved by asymmetric slots and slits cut along the diagonal and orthogonal directions of the patch radiator. The asymmetric slotted-slit-microstrip on the RIS structure is used for further miniaturization of the antenna with CP radiation. The measured results of the proposed antenna are 2.1% (2.625–2.68 GHz) for 3-dB axial ratio bandwidth, 9.5% (2.575–2.82 GHz) for 10-dB return loss bandwidth, and 3.87 dBic for gain at the boresight. The patch radiator size is 0.187 λ × 0.179 λ on a low cost FR4 substrate at 2.6 GHz.